If (Virtual) Reality Feels Almost Right, It’s Exactly Wrong - Gonzalez Franco, Mar; Berger, Christopher C; Hinckley, Ken (Scientific American, 2018)
We can all remember the crisply beveled edges of our cheery-yellow No. 2 pencil, the cool, smooth feel of a chalk-powdered blackboard, the gritty red bricks of the schoolhouse walls. Surely that all wasn’t just an illusion? No, of course not. But—as it turns out—it kind of is.